Woman in Icelandic dress, Pembina County, N.D. (Pembina County Historical Society;)
Woman dressed in native Icelandic costume, probably used at the Icelandic celebration of the Deuce of August in the 1950s. The woman has a white dress on with a gold belt. A blue cape line with fur wraps around her. She also wears a white veil with a gold head piece, and white high heeled shoes. Color photographic prints; 25 x 20 cm. Title created by staff. Photographer unknown. By 1874, Iceland had been under harsh Danish rule for hundreds of years and the people wanted their freedom. A man named Jon Sigurdsson was determined to get it for them. In the summer of 1874 the Danish King, King Kristjan the Ninth, visited Iceland and the Icelandic Parliament was called into session from August the first to the seventh. On August the Second, he handed over the New Constitution to the Parliament and every Icelandic church held a service. In the early 1870s a small group of Icelandic people immigrated to Milwaukee, Wisconsin and celebrated on August 2, 1874. The Icelandic community in Winnipeg had their first celebration on the August 2, 1890, calling it "The Day of the Icelanders." Icelandic communities continue to celebrate The Deuce of August to celebrate their heritage and share cultural roots. Information from http://www.august2nd.com/index.html